‘What a perennial delight is in hearing the French language spoken!’: Class, Language and Taste in the Maison de Molière’s French Performances in London (1871–1893) - Ignacio Ramos Gay (Cahiers Victoriens et Edouardiens)
In 1879, theatre critic Augustin Filon stated on account of the French company’s second visit to London that year, ‘les voyages de la Comédie-Française sont regardés en Angleterre comme des dates’. Upon receiving the troupe, renowned actor Henry Irving praised the success of French actors, such as Got, Mounet-Sully, Coquelin aîné and cadet, and Sarah Bernhardt on the Gaiety Theatre stage in London. Their performance in their native tongue proved to be an aesthetic magnificence that had clearly captivated an essentially English-speaking audience: ‘the pictures they produced went straight to the heart and needed no language for those of us who could not master French’, Irving declared. Indeed, performances in the original linguistic version were sure to garner critical acclaim. British actor and theatre director Sir Herbert Beerbohm Tree would also chime in to eulogize the prosodic qualities of the language of Molière, contrasting it with the British tradition as follows: ‘what a perennial delight is in hearing the French language spoken! . . . How blunt and heavy an old instrument, in comparison, English seems!’ For their powerful oratory and elocution on stage, the French, he concluded, were ‘a naturally expressive race’. This study aims to analyse the impact of the Comédie-Française in Victorian England by focusing on the company’s visits to London in 1871, 1879 and 1893. Although their repertoire (which included works by Molière, Racine, Corneille, Alfred de Musset, Alexandre Dumas fils, and Émile Augier) was completely performed in French, the company was commended by audiences as much as it was lauded by British professional peers, for whom it represented the ultimate expression of high art. Through an examination of the reviews and impressions published by an array of professionals, including leading theatre critics at the time, dramatists, actors and aficionados, the research analyses the sociological, political, and aesthetic implications associated with the firm presence of the French language and French canonical plays in late Victorian London. The responses of theatre professionals inevitably raise the matter of high art by implicitly questioning which of the two theatrical traditions best reflect and recreate, through their language, such cultural standards: How is a language stylized to answer simultaneously to dramatic conventions and to expectations related to national sentiment? To what extent could French phonetics and prosody be regarded as a sociocultural referent accessible only to an elite audience? Did the Lord Chamberlain subject the plays in French to the same censorship procedures and vigilance as those in English? By posing these and other related matters, the work argues that the debate on the superiority of French or English as theatrical languages is inevitably bound to the ever-fluctuating issue of Britishness. Theatre being a fundamental pillar of national identity (while also an indispensable conduit for questioning political order and structures), the traditional rivalry between French and British culture could not have found a better setting in which to compete for aesthetic and rhetorical excellence than the London stage.